Pengaruh Efektivitas E-Learning Terhadap Hasil Belajar Fiqih Siswa Kelas VIII MTsN 11 Jombang - Farida Infirochah (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
E-learning can provide effective learning methods such as feedback related to collaborative independent learning activities, as well as personalized learning based on student needs. Therefore, this study aims to determine the effect of the effectiveness of e-learning on the fiqh laerning outcomes of class VIII MTsN 11 Jombang students. The research mehod used is a quantitative approach that is expost facto, data collection using questionnaires and documentation using a sample of 40 students. And analyzes using the SPSS 16.0 application. The results of thisstudy indicate that there is no correlations between the effevtiveness of e-learning and the fiqh learning outcomes of class VIII MTsN 11 Jombang Students with a significant value of 0.789 > 0.05. and there are alse several supporting factors from this research that are not in line with the existing theory. So the conclusion of this study is that there is no correlation between the effevtiveness of e-learning and the learning outcomes of fiqh class VIII MTsN 11 Jombang.